An Efficient Bivalent Cyclic RGD-PIK3CB siRNA Conjugate for Specific Targeted Therapy against Glioblastoma In Vitro and In Vivo - Bohong Cen; Yuanyi Wei; Wen Huang; Muzhou Teng; Shuai He; Jianlong Li; Wei Wang; Guolin He; Xin Bai; Xiaoxia Liu; Yawei Yuan; Xinghua Pan; et al. (Elsevier, 2018)
The PI3K-AKT-mTOR-signaling pathway is frequently activated in glioblastoma (GBM). Inhibition of phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit beta (PIK3CB)/p110β (a PI3K catalytic isoform) by RNAi substantially suppresses GBM growth with less toxicity to normal astrocytes. However, insufficient and non-specific small interfering RNA (siRNA) delivery may limit the efficacy of RNAi-based therapies against GBM. Here we prepared a novel methoxy-modified PIK3CB siRNA molecule (siPIK3CB) that was covalently conjugated to a [cyclo(Arg-Gly-Asp-D-Phe-Lys)-Ahx]2-Glu-PEG-MAL (biRGD) peptide, which selectively binds to integrin αvβ3 receptors. The αvβ3-positive U87MG cell line was selected as a representative for GBM. An orthotopic GBM xenograft model based on luciferase-expressing U87MG was established and validated in vivo to investigate bio-distribution and anti-tumor efficacy of biRGD-siPIK3CB. In vitro, biRGD-siPIK3CB specifically entered and silenced PIK3CB expression in GBM cells in an αvβ3 receptor-dependent manner, thus inhibiting cell cycle progression and migration and enhancing apoptosis. In vivo, intravenously injected biRGD-siPIK3CB substantially slowed GBM growth and prolonged survival by reducing tumor viability with silencing PIK3CB expression. Furthermore, biRGD-siPIK3CB led to mild tubulointerstitial injury in the treatment of GBM without obvious hepatotoxicity, whereas co-infusion of Gelofusine obviously alleviated this injury without compromising anti-tumor efficacy. These findings revealed a great translational potential of biRGD-siPIK3CB conjugate as a novel molecule for GBM therapy. Keywords: siRNA delivery, gene silencing, orthotopic glioblastoma, tumor targeting